Hydatigera parva population genetics in Iberian rodents provides insights into its introduction from Africa - Milan Miljević; Marija Rajičić; Javier Marco; Jelena Blagojević; Ruth Rodríguez-Pastor; Branka Bajić; Javier Millán (Parasitology)
This study investigated the prevalence and genetic diversity of Hydatigera parva in 341 native rodents in a riparian habitat in the Mediterranean part of Spain. Polycephalic larvae were found in 32% of wood mice (Apodemus sylvaticus; n = 84) and 0.4% of Algerian mice (Mus spretus; n = 257) examined, with a significantly higher prevalence in the former. No significant differences in infection prevalence in wood mouse were found between sex and age groups, habitats (agricultural vs natural) or seasons. Genetic analysis of 25 cysts using cox1 sequences revealed low nucleotide (0.00110) and haplotype diversity (0.380), suggesting limited genetic variation. Phylogenetic analysis showed that the studied H. parva isolates were genetically distinct from other species within the genus Hydatigera. The results indicate a lower genetic diversity in European than in African populations, supporting the hypothesis that H. parva was introduced to Europe from Africa, possibly with its final host, the common genet (Genetta genetta), an abundant predator in the study area. This study is the first population genetic study of H. parva in the Iberian Peninsula. It provides insights into the population structure of the parasite and its interaction with rodent hosts, and thereby constitutes an example of the potential identification of an introduction route of a parasite with its definitive host. It also confirms the importance of the wood mouse as an intermediate host for the maintenance of the parasite’s life cycle in Europe and forms the basis for further studies on the distribution and genetic diversity of H. parva.